The effect of perceived organizational politics on responses to job dissatisfaction: The moderating roles of self‐efficacy and political skill. Issue 2 (16th August 2021) - Atshan, Nadia A.; Al‐Abrrow, Hadi; Abdullah, Hasan Oudah; Khaw, Khai Wah; Alnoor, Alhamzah; Abbas, Sammar
Abstract: A high level of perceived organizational politics can lead to adverse consequences for the organization. This article examines the impact of perceived organizational politics on responses to job dissatisfaction by considering the moderating role of self‐efficacy and political skill using data from a sample of 202 health sector staff in Iraq. The results show that self‐efficacy and political skill are moderators in the relationship between perceived organizational politics and staff responses to job dissatisfaction. Using measures based on four responses to job dissatisfaction–voice, loyalty, neglect, and exit–the study found that there was a moderative role for self‐efficacy related to the dimensions of silence and loyalty, and a moderative role for political skill related to the dimensions of silence, voice, and loyalty. There was no moderating role for the exit dimension. The article concludes with several suggestions for how to deal with the adverse consequences of high levels of perceived organizational politics.